2018
DOI: 10.4322/acr.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injury to the internal carotid artery by the hyoid bone: a rare cause of ischemic stroke

Abstract: Central nervous system (CNS) ischemic events, besides being a common and devastating disease, are accompanied by severe disability and other morbidities. The cause of such events is not always that simple to diagnose, and among the young, a broad spectrum of possibilities should be considered. We present the case of a young man who presented two episodes of CNS ischemia with a 1 year gap between them, which occurred in the same situation while he was walking and carrying a heavy backpack. The second event firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Its position in the neck relative to the carotid arteries can shift, as evidenced by reports of arterial injury by the hyoid bone after repetitive trauma, such as carrying heavy weights and playing golf. 2,8,12 The compression of the carotid artery by the hyoid can cause abrupt geometric wall changes to the artery that result in disturbed flow and high wall shear stress gradients. 13 The susceptibility to atherosclerosis at the carotid bifurcation, a location where the vessel geometry changes from straight to branched, is an example of the correlation between wall stress and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its position in the neck relative to the carotid arteries can shift, as evidenced by reports of arterial injury by the hyoid bone after repetitive trauma, such as carrying heavy weights and playing golf. 2,8,12 The compression of the carotid artery by the hyoid can cause abrupt geometric wall changes to the artery that result in disturbed flow and high wall shear stress gradients. 13 The susceptibility to atherosclerosis at the carotid bifurcation, a location where the vessel geometry changes from straight to branched, is an example of the correlation between wall stress and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic carotid artery disease caused by hyoid bone intrusion is an extremely rare phenomenon. Scant reports have detailed the cerebrovascular events due to mechanical interference of the hyoid bone on the carotid artery leading to entrapment, 1-3 embolism, [4][5][6][7][8][9] dissection, 6,10 atherosclerotic stenosis, 11 and pseudoaneurysm formation. 12 In some cases of embolism or dissection, the patients were treated medically, 4,7,10 whereas other patients with compression, pseudoaneurysm, or stenosis underwent surgical management with partial resection of the hyoid bone.…”
mentioning
confidence: 99%
“…10) We found that 17 ACVS cases due to HB obstruction have been reported previously. Among these reports, we summarized cases in which we identified the running course of the ICA (medial or lateral to ECA) and the positional relationship between HB and ICA 1,[11][12][13][14][15][16][17][18][19][20][21][22] (Table 1). Among 14 cases, seven cases had twisted carotid bifurcations, and in all the cases the greater horn of HB was located lateral to the ICA.…”
Section: Nmc Case Report Journal Vol 8 2021mentioning
confidence: 99%